2010
DOI: 10.1016/j.ejcts.2009.07.003
|View full text |Cite
|
Sign up to set email alerts
|

NT-pro-BNP, but not C-reactive protein, is predictive of atrial fibrillation in patients undergoing coronary artery bypass surgery

Abstract: Preoperative and postoperative NT-pro-BNP as well as TnT values were significantly higher in patients who subsequently developed AF. TCLG and CRP were not useful in identifying patients at higher risk for AF. Multivariate analysis identified age, preoperative NT-pro-BNP and duration of CPB as independent correlates of AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
3
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 25 publications
2
38
3
2
Order By: Relevance
“…They concluded that preoperative NT-pro-BNP, duration of cardiopulmonary bypass and advanced age were the independent predictors. 34 Iskesen I, et al reported the same situation and concluded the positive correlation between high levels of preoperative NT-pro-BNP and risk of new-onset AF after conventional CABG. 35 Kerbaul F reported that preoperative and postoperative NT-pro-BNP levels after OPCAB could predict cardiovascular complications.…”
Section: -23�mentioning
confidence: 78%
“…They concluded that preoperative NT-pro-BNP, duration of cardiopulmonary bypass and advanced age were the independent predictors. 34 Iskesen I, et al reported the same situation and concluded the positive correlation between high levels of preoperative NT-pro-BNP and risk of new-onset AF after conventional CABG. 35 Kerbaul F reported that preoperative and postoperative NT-pro-BNP levels after OPCAB could predict cardiovascular complications.…”
Section: -23�mentioning
confidence: 78%
“…Significant associations between dense spontaneous echo contrast and the 2 indexes, Creactive protein and soluble P-selection, support the hypothesis of increased inflammatory activity for thrombogenesis in AF (5). Inflammatory markers play an important role in the development of AF, although the results are not consistent (3). An association of preoperative platelet activity and POAF has been shown previously (21,22).…”
Section: Commentmentioning
confidence: 86%
“…Due to the lack of data describing the time point when POAF occurred after CABG in our analysis, one could argue against our hypothesis of an association between POAF and HAPR. When analyzing the available data on the time association of POAF and open-heart surgery, most reports indicate the highest incidence within the first 4 days following the procedure, peaking around the second day (3,20). Therefore, if the timing of postoperative PFT was synchronized with the timing of POAF, the association effect of POAF and HAPR could only have been stronger.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…I am very glad to see that Dr Shih et al reported my case of haemomediastinum caused by a ruptured bronchial artery aneurysm [1]. This is one of the bronchial arterial embolisation cases that I performed during October 2006.…”
mentioning
confidence: 94%